1998
DOI: 10.3109/09638289809166073
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of self-efficacy among persons with spinal cord injuries

Abstract: The purpose of this study was to determine the factors affecting self-efficacy among persons with spinal cord injury (SCI). The study population consisted of 105 persons with SCI who were discharged from one of eight hospitals in north central Alabama between October 1989 and September 1992. Data were derived from a retrospective acute-care medical record review and 12-month annual follow-up telephone interviews. The findings indicate that high self-efficacy is significantly associated with less severe neurolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 17 publications
1
9
1
3
Order By: Relevance
“…Evidence is fairly strong that SE and PC are not related with sociodemographic and lesion-related variables. Associations of belief-related resources with sociodemographic variables such as education, 25,26,31,34,36,41 gender, 25,26,31,36 age, 25,26,29,31,36,41,46,48 marital status, 25,26,36,49 income 25,26 and ethnicity 26,28,36 were largely not significant.…”
Section: Resultsmentioning
confidence: 88%
“…Evidence is fairly strong that SE and PC are not related with sociodemographic and lesion-related variables. Associations of belief-related resources with sociodemographic variables such as education, 25,26,31,34,36,41 gender, 25,26,31,36 age, 25,26,29,31,36,41,46,48 marital status, 25,26,36,49 income 25,26 and ethnicity 26,28,36 were largely not significant.…”
Section: Resultsmentioning
confidence: 88%
“…The results from other studies on the relationship between marital status and self-management or self-efficacy are mixed. Some studies have outlined associations between being married and better self-management of various chronic diseases [32,33], whereas other studies have found higher self-efficacy among patients who were unmarried [34] or divorced [35]. Still other studies have found no association between marital status and the self-management of chronic illnesses [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Samoefikasnost je povezana i s nizom subjektivnih tjelesnih simptoma (Hudek-Knežević i Kardum, 2009). Nakon što su kontrolirani sociodemografski pokazatelji i stupanj doživljenog stresa, niža razina samoefikasnosti bila je povezana sa simptomima kronične iscrpljenosti (Findley, Kerns, Weinberg i Rosenberg, 1998), a kros-sekcijski i retrospektivni podaci dobiveni godinu dana nakon otpuštanja iz bolnice pokazali su da je viša samoefikasnost povezana s manjim brojem subjektivnih neuroloških simptoma kod pacijenata s ozljedom leđne moždine (Horn, Yoels, Wallace, Macrina i Wrigley, 1998). Meta-analitičko istraživanje pokazuje da je viša samoefikasnost zaštitni faktor od izgaranja na poslu kod nastavnika i zdravstvenih djelatnika (Shoji i sur., 2016).…”
Section: Percipirana Samoefikasnost I Zdravstveni Ishodiunclassified